Bacterial fish pathogens - Austin, B. (Ellis Horwood, 1993)
Bacterial Fish Pathogens was planned to fill the need for an up - to -date comprehensive text on the biological aspects of the bacterial taxa which cause disease in fish. The scope of the book covers all the bacterial taxa which have at one time or another been reported as fish pathogens.